Exploring hotel managers perceptions and responses as counter measures for seasonality – a sustainable framework for Kenya’s tourism industry - Eleri, Jones; Burugu, Rose; Wishitemi, Bob; Kiprutto, Nehemiah (Strathmore University, 2014)
Seasonality in tourism has continued to be a concern for researchers, managers, policy makers and the hotel industry globally. Kenya is typified by a two-peak seasonality pattern, which is often characterized by the nature of tourist seasons. In terms of measuring seasonality patterns and managers responses, a plethora of previous studies have measured its impacts, scale, duration and recurrence, from the point of view, of either analyzing: tourist traffic in and out of hotels and other enterprises; the number of workers laid-off or employed; the hotels ability to profitably maintain business operations all-year round. Due to the consistency and predictability of seasonality patterns, hotel managers have continuously responded by either coping, challenging or capitulating. Despite the extensive awareness of the problem, very few studies have focused on the effects of managers‟ perceptions or explored non-competitive and sustainable strategic frameworks to be adopted by hotel managers‟. By using a low-cost and differentiated strategic framework, a qualitative research which employed a multiple case study design, was used to shade some light on managers responses, solutions and perceptions. This paper largely relies on a 2013-2014 qualitative research of 17 hotels in the South Coast of Kenya. The results show that there is a potential for a new and sustainable shift of the problem in the future. It recommends that investors as well as hotel managers should be more receptive to creativity and investment in unrivalled products and services through value-innovation.
Conference paper presented at the 1st African Conference on Sustainable Tourism in Strathmore University, Kenya.
Keywords: Seasonality; Tourism; Tourism Industry; Kenya; Management